Influência do Programa Bolsa Família e renda no controle da pressão arterial de hipertensos atendidos na atenção primária à saúde - Buchmeier, James Silva Moura (2014)
Cardiovascular diseases are the major cause of death in the planet, and Systematic Arterial Hypertension (SAH) is one of the main grievances of these diseases. Among the modifying factors for SAH, the individual or family income plays an important role in blood pressure control. Among the main contributions it is the income transfer programs, such as the Bolsa Família Program (PBF) of the Brazilian government. Therefore, the main goal of this study was to analyze the effect of income transfer assistance programs and income on controlling systematic arterial hypertension in adult users registered in the HIPERDIA Program in the city of Joao Pessoa. Income was divided into four groups (G1, which received Bolsa Familia and cutouts for G2, G3 and G4). This is a qualitative and quantitative study. The first is characterized by an observational study, cross-sectional for the year of 2009. In the qualitative approach it was used the Collective Subject Discourse (CSD) as method. The studied variables represent socio-demographic, anthropometric hemodynamic features of hypertensive patients. For statistical analyzes it was used the Variance Analyzes test (ANOVA) with post hoc Tukey-HSD; the Kruskal-Wallis test with post hoc of Dunn; the t Student test, the Mann-Whitney test and the Wilcoxon test. For the risk factors analyzes it was used the Logistic Generalized Linear Model. The profile of the representative sample was predominant in females, race/skin color not white, married, who have studied until high school, employed, with little advantage in controlled Blood Pressure (BP), high risk of waist circumference, low risk of waist-to-hip ratio (WHR) and normal Body Mass Index (BMI). The test of averages resulted in statistical differences between the four groups for the variables: age and systolic blood pressure. The factors that worked in the BP control were: G1, age (OR = -1,15) and males (OR = 0,89); in group G2 sex (OR = -1,29) and BMI (OR = 1,94); group G4 marital status being married (OR = 1,75) and body mass (OR= 0,50). In the qualitative phase it was observed that most individuals use allopathic medicines to control SAH and they clearly claimed that the funds provided by the PBF was not enough to control blood pressure in hypertensive individuals, whose money was spent on things for the house. It is suggested that there is no evidence that the PBF influences blood pressure control in hypertensive patients enrolled in the Hiperdia Program, in the city of Joao Pessoa during the study period.